Correct name for the Asian Brown Flycatcher (Aves: Muscicapidae, Muscicapa) - Mlíkovský, Jiří (Zootaxa, 2012)
Broad-billed flycatchers of East Siberia, which migrate to winter in south-east Asia south to the Greater Sunda Islands, were first described as new for science by Raffles (1822: 312) from Sumatra under the name Muscicapa latirostris. The species was known as Muscicapa latirostris Raffles (or latirostris in combination with other generic names) for over a century (e.g. Dresser 1902: 252, Hartert 1907: 477, Vaurie 1959: 331), but since the 1930s it has been called either Muscicapa latirostris Raffles or Muscicapa daurica Pallas (see below for the history). This dichotomy continues; some authors prefer latirostris (e.g. Peklo 1987; Stepanân 1990, 2003; Nakano & Murakami 2001; Popov 2004; Kwon et al. 2006; Takeuchi 2007; Kolbin 2008; Gavrilov 2011; Sonina & Durnev 2011), while others prefer daurica (e.g. Banks & Browning 1995; Clarke et al. 2009; Tojo 2009; Mohan & Kumar 2010; David 2011).